The development of novel N-heterocyclic carbenes for asymmetric C-C bond forming reactions - DiRocco, Daniel A., author; Rovis, Tomislav, advisor; Williams, Robert M., committee member; Finke, Richard G., committee member; Bailey, Travis S., committee member; Chatterjee, Delphi, committee member (Colorado State University. Libraries, 2012)
A variety of novel N-heterocyclic carbenes have been developed as organocatalysts for highly efficient and selective intermolecular C-C bond forming reactions. Problems associated with attaining high selectivity while retaining high efficiency in asymmetric intermolecular acyl anion pathways have been resolved through non-traditional manipulation of the catalyst architecture. In the context of the asymmetric intermolecular Stetter reaction, a new series of fluorinated triazolium salt pre-catalysts have been developed that catalyze the highly enantioselective coupling of hetaryl aldehydes and nitroalkenes. Stereoelectronic effects in the ground state suggest that conformation of the catalyst plays a role in determining selectivity. DFT calculations provide evidence for an electrostatic interaction between the fluorine-induced dipole and the electrophiles as the source of increased selectivity. The scope of the asymmetric intermolecular Stetter reaction of nitroalkenes has been further expanded to incorporate α,β-unsaturated aldehydes as partners. Mechanistic studies point to the initial proton-transfer event leading to generation of the acyl-anion equivalent as being turnover limiting. With this knowledge, an additive has been introduced that effectively increases the rate of proton transfer leading to substantially shorter reaction times and dramatically lower catalyst loadings. Further catalyst development has led to the realization of another mode of catalyst control, using the C-F bond as an additional source of substrate differentiation. This complementary fluorinated catalyst architecture substantially increases the reactivity of enolizable aldehydes in the asymmetric intermolecular Stetter reaction of nitrostyrenes, and for the first time allows for their inclusion in this transformation. An asymmetric aza-benzoin reaction of aliphatic aldehydes and N-Boc imines has been developed after identifying an extremely selective amino-indanol derived catalyst scaffold and mild reaction conditions. The direct enantioselective acylation of amines has been realized using a dual catalysis manifold, incorporating a photoactive metal complex as a catalyst to activate amines toward acyl-anion addition and a chiral NHC catalyst. This methodology has led to the isolation and full characterization of a series of aza-Breslow intermediates by X-ray crystallography. Studies of these intermediates provide crucial information about the fundamental reactivity of the Breslow intermediate and show that it is not only a catalyst resting state in these transformation but its generation is also reversible in the presence of a weak acid.